ENDOTHELIAL DYSFUNCTION IN TRANSIENT ISCHEMIC ATTACK IN THE VERTEBRAL-BASILAR SYSTEM - Henyk, S. I.; Gryb, V. A.; Maksymchuk, L. T.; Doroshenko, O. O.; Henyk, Ya. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Transient ischemic attack (TIA) in the vertebral-basilar system (VBS) is characterized by an acute onset of focal neurological symptoms due to short-term local ischemia of the brain. According to various authors, temporary neurological manifestations of circulatory insufficiency in VBS can progress to complete stroke within 2-5 years in 30-50% of patients, leading to disability of about 80% of patients. Its diagnosis is associated with some difficulties due to the variability of clinical manifestations, clinical similarity with other diseases and, as a consequence, incorrect therapeutic tactics. The aim of the study was to investigate changes of endothelial function in TIA in VBS by determining the levels of homocysteine (HC) and vascular endothelial growth factor (WEGF) at different stages of neurological deficiency (ND). 78 patients with TIA in VBS were examined. The questionnaire developed by us was used to determine the stage of ND in TIA. The level of HC was determined by enzyme-linked immunosorbent assay. WEGF was determined using the "sandwich" method of enzyme-linked immunosorbent assay. In the group of patients with stage I ND, a tendency to HC increase in 1.1 times was detected compared with almost healthy persons (AHP), stage II - HC increased in 1.5 times (p <0.05), and stage III - in 1.9 times (p <0.05). Also significant difference (1.8 times) was revealed at stage III compared to the index of stage I (p <0.05). WEGF at the 1st stage of ND significantly increased in 1,7 times in comparison with AHP (p <0.05), at the 2nd stage there was a tendency to increase (in 1.2 times), at the 3d stage there was a significant increase in WEGF in comparison with AHP (in 2.9 times) (p <0.05), and compared with indicators of I (in 1.8 times) (p <0.05) and II stages (2.6 times) (p <0 , 05). We have shown that TIA in VBS is accompanied by endothelial dysfunction (increase in HC and WEGF), which is more pronounced with aggravation of the ND. To evaluate the prognosis of the disease, we recommend using a questionnaire for determination the stage of ND in TIA in VBS and to identify markers of endothelial function such as HC and WEGF.